Tablet technology integration framework for slow learner learning - Hassan, Azizzeanna; Mahmud, Murni; Md Tap, Abu Osman (IEEE, 2014)
Tablet technology is the latest mobile swipe-touch base technology that interest by many groups of people. The technology uses the mechanism of multi-touch screen, which are fingers to interact with the application, gives the confidence of the student including the special needs student to feel more motivated to stay put in longer period and engage with the application. Slow learners are a group of learning disabilities children may also be able to benefits the tablet technology in their learning. It is essential to obtain support from the teachers to integrate the tablet technology in the slow learners' learning. To realize the integration, this study proposing a framework for including the tablet technology in to the learning of slows learners.